Fiziceskaja podgotovlennost' kvalificirovannych futbolistov razlicnych igrovych amplua - Psibil'skij, V.; Jastzembskij, Z. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of the research was the analysis of the range of individual distinctions in the basic parameters of physical preparedness and their differences connected to the game position in elite football players. The surveyed players were of 26,4±5,1 (20-37) years of age. The monitoring of training loads was carried out in the research. It is possible by results of the research to agree with the point of view, that the versatility of football players as the tendency of their development with the reference to physical training should go in two ways: 1) the equal perfection of all major components of special physical preparedness; 2) the profound perfection of only separate components where are some inclinations. Such approach assumes an economization and individualization of physical training, being guided by principles of the optimization of the structure of physical preparedness, which demands the further development. Such approach creates more favorable conditions for the realization of technical-tactical and intellectual potentials of players of different game positions.